The Effectiveness of Quizizz Application to Improve English Reading Comprehension - Susilawati; rinaepi; Rika Septiani (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2025)
The research on this thesis is motivated by the difficulty of students in reading comprehension of English text. There are still many students who have difficulty in understanding the contents of an English text that makes students not enthusiastic about learning so that student motivation is also influential, by using the Quizizz application researcher hope that students will increase in reading comprehension. The purpose of this study was to collect direct evidence about to determine the use of Quizizz application can improve students ' reading comprehension, Saturated sampling technique was used by the researcher. The study used a sample of 52 students: 25 students in the experimental class and 27 students in the control class. The method used in this study is a quantitative method and the design used in this study is a quasi-experimental study. The Data were analyzed using IBM SPSS version 29 and obtained using tests, observations, and documentation. The researcher used a pretest and posttest consisting of 20 multiple choice questions in the data collection, and the researcher also makes a checklist observation sheet .1) in analyzing the data, the researcher used a t-test results from the calculation showed that the significance level of 5% is (7,545 > 2,086). This means that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. The results of the test criteria showed that students ' vocabulary mastery using and without the Quizizz application was significantly different. This is indicated by a higher average score for the experimental class compared to the control class. Therefore, it can be concluded that Quizizz application help students Class X TKJ SMK AUTOMATSUDA in English reading comprehension.